Fetal renal cystic disease and post-natal follow up—a single center experience - Botero-Calderon, Lorena; Lawrence, Anne; O’Toole, Natalie; Guay-Woodford, Lisa M. (Frontiers in Pediatrics, 2023)
Introduction: Prenatal sonographic evidence of large, echogenic, or cystic kidneys may indicate any one of a diverse set of disorders including renal ciliopathies, congenital anomalies of the kidney and urinary tract (CAKUT), or multisystem syndromic disorders. Systematic transition planning for these infants from in utero detection to post-natal nephrology management remains to be established.Aim of the work: We sought to evaluate the presentation and transition planning for infants identified in utero with bilateral renal cystic disease.Methods: Our retrospective observational study identified 72 pregnancies with bilateral renal cystic disease in a single center from 2012 to 2022; 13 of which had a confirmed renal ciliopathy disorder. Clinical and imaging data, genetic test results, and documentation of postnatal follow-up were collected and compared.Results: In our suspected renal ciliopathy cohort (n=17), autosomal recessive polycystic disease (ARPKD) was the most common diagnosis (n=4), followed by Bardet-Biedl syndrome (BBS, n=3), autosomal dominant polycystic disease (ADPKD, n=2), HNF1B-related disease (n=2), and Meckel-Gruber syndrome (MKS, n= 2). Four cases were not genetically resolved. Anhydramnios was observed primarily in fetuses with ARPKD (n=3). Polydactyly (n=3) was detected only in patients with BBS and MKS, cardiac defects (n=6) were identified in fetuses with ARPKD (n=3), MKS (n=2), and BBS (n=1), and abnormalities of the CNS (n=5) were observed in patients with ARPKD (n=1), MKS (n=2), and BBS (n=3).In general, documentation of transition planning was incomplete, with post-natal nephrology management plans established primarily for infants with renal ciliopathies (n=11/13; 85%). This is a provisional file, not the final typeset article Conclusion: Prenatal sonographic detection of echogenic kidneys should raise suspicion for a broad range of disorders, including renal ciliopathies and CAKUT. Multicenter collaboration will be required to standardize the implementation of transition guidelines for comprehensive nephrology management of infants identified in utero with enlarged, echogenic kidneys.